The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.20463/pan.2022.0006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological systemic analysis of gardenia fructus against non-alcoholic fatty liver disease and validation of animal models

Abstract: [Purpose] We aimed to investigate the systemic pharmacological analysis of gardenia fructus (GF) and the proof of concepts. We examined the antioxidant and anti-inflammatory effects in high-fat (HF) diet mice.[Methods] The active compounds of GF and the target genes were identified using the Traditional Chinese Medicine Database and Analysis Platform (oral bioavailability ≥ 30%, Caco-2 permeability ≥ -0.4, and drug-likeness ≥ 0.18). The rats were divided into four groups: untreated group, HF group, HF and metf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Scorletti et al reported that the continuous storage of lipid droplets induces NFALD 15 . As shown in Figure 2, our re-Figure 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scorletti et al reported that the continuous storage of lipid droplets induces NFALD 15 . As shown in Figure 2, our re-Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the components of EB and the target gene network, we used the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) and Cytoscape. EB characteristics analyze of EB was analyzed as previously described [ 15 ]. The TCMSP ( http://ibts.hkbu.edu.hk/LSP/tcmsp.php ) was used to identify the active components of EB.…”
Section: Methodsmentioning
confidence: 99%
“…To confirm the effects of RMF in the NAFLD mouse model, tissues were analyzed using a staining solution and specific antibodies. Immunohistochemistry was performed as previously described [ 16 ]. First, the mice were perfused and fixed in 10% formalin.…”
Section: Methodsmentioning
confidence: 99%
“…It has been recently reported that natural products, including phenols, flavonoids, glycosides, quinones, terpenoids, pyrazines, alkaloids, and phenylpropanoids, have antioxidant, energy-producing, anti-inflammatory, anti-apoptotic, and anti-aging effects, which mainly influence the AMPK/Nrf2/mTOR, Nrf2/HO-1, NAMPT/NAD(+)/SIRT, AMPK/SIRT1/PGC-1alpha and PKCs/PARPs/NF-kB signaling pathways, thereby regulating NAD(+) metabolism to prevent and treat NAFLD [ 117 ]. Hepatoprotective effects, caused by the inhibition of PI3K/Akt/mTOR signaling and effective alleviation of oxidative stress damage and ER stress induced by excessive lipid accumulation in hepatocytes, and activation of autophagy were observed for agonists of AMPK thymoquinone [ 118 ] and 5-aminoimidazole-4-carboxamide-1-beta-D-ribofuranoside (AICAR) [ 119 ], agonist of GLP-1/glucagon cotadutide [ 120 ], an antagonist of sphingosine 1-phosphate receptor 2 (S1PR2) JTE-013 [ 26 ], activator of PI3K, autophagy-related genes (ATG) and agonist of Nrf2, PPARα and hemeoxygenase-1 (HO-1) pterostilbene [ 121 ], flavonoid with antioxidant properties involving CYP7A1, quercetin [ 122 ], Pueraria flavonoids [ 92 ], a novel gerotherapy compound, BIOIO-1001 [ 123 ], a natural nonenzymatic antioxidant with low toxicity schisandrin B (Sch B) [ 124 ], H1-antihistamines (AHs) [ 125 ], fat soluble polyphenol Tanshinone IIA (TsIIA) [ 126 ], purendan (PRD) [ 127 ], down-regulating the expression of p-mTOR, p-S6K1 and SREBP-1c, chrysin [ 128 ], red pepper seed extract (RPS) [ 129 ], Gardenia Fructus (GF) extracts [ 130 ], curcumin [ 131 ], and magnesium [ 132 ].…”
Section: New Therapeutic Approaches and Molecular Targets In Nafld/na...mentioning
confidence: 99%
“…In a recent study, a dual inhibitor of soluble epoxide hydrolase (sEH) and cyclooxygenase 2 (COX-2), 4-(5-phenyl-3-{3-[3-(4-trifluoromethylphenyl)-ureido]-propyl}-pyrazol-1-yl)-benzenesulfonamide (PTUPB), significantly reduced the expression of liver senescence-related molecules p16, p53, and p21 in HFD mice and inhibited the PI3K/AKT/mTOR pathway through Sirt1 [ 130 ]. PTUPB improved autophagy, slowed down the senescence of hepatocytes, and alleviated NAFLD in vitro [ 133 ].…”
Section: New Therapeutic Approaches and Molecular Targets In Nafld/na...mentioning
confidence: 99%